Is the project management field suffering from methodological inertia?: Looking for evidence in publications in a recently established journal - Scales, J.; Sankaran, J.; Cameron, Roslyn (EURAM, 2015)
Project management (PM) researchers have traditionally used quantitative methods in their research due to the origins of this practice-based discipline in defence and engineering. Although qualitative methods are starting to be used in PM research, most of the qualitative research reported tends to use case studies. Recently, there has been a call for PM researchers to use more novel methods to increase the variety of methods used by the researcher in the field contributing to its further development (Drouin, Muller and Sankaran 2013; Cameron, Sankaran and Scales 2015). A review of papers presented at the International Research Network on Organizing by Projects (IRNOP) conference in Berlin in 2009 showed a surprising trend that papers presented at these conferences used more qualitative methods in comparison with articles published in key PM journals. This paper analyses articles published over the past six years in a comparatively new PM journal, since its inception, to explore whether the new journal has motivated PM researchers to overcome their methodological inertia and broaden the variety of research methods they use. A mixed methods prevalence study was undertaken on articles published in the International Journal of Managing Projects in Business (IJMPiB) from 2008 to 2014 (n=265). The findings point to methodological inertia in the majority of research but also an unusually high proportion of the use of mixed methods. Future research is needed to add finer granularity to the analysis.